Comparative analysis of the efficacy and safety of fixed-dose combinations versus their individual components for open-angle glaucoma - Z.M. Nagornova; A.V. Kuroyedov; A.V. Seleznev (РМЖ "Клиническая офтальмология")
Z.M. Nagornova1, A.V. Kuroyedov2,3, A.V. Seleznev1 1Ivanovo State Medical Academy, Ivanovo, Russian Federation 2 Central Military Clinical Hospital named after P.V. Mandryka, Moscow, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation Currently, various glaucoma medications are available at the pharmaceutical market. Among them, fixed-dose combinations are of special importance which are considered as first-line agents for some patients (i.e., with advanced glaucoma or high intraocular pressure). Fixed-dose combinations are superior to individual components through the comfortable regimen with less instillations which improves treatment compliance. Moreover, IOP-lowering effect of fixed-dose combinations is similar or even greater than that of individual components due to the lack of washout phenomenon and less toxic effect of preservatives on the ocular surface. However, there are several disadvantages of fixed-dose combinations, e.g., dosing and regimen are inflexible and cannot easily be regulated. The paper discusses the results of clinical trials which compare the efficacy and safety of the most common fixed-dose combinations and their individual components. Thus, fixed-dose combinations of prostaglandin analogues and timolol maleate demonstrate similar IOP-lowering effect as compared with individual components and less side effects. Keywords: primary open-angle glaucoma, fixed-dose combination, glaucoma, combined therapy, treatment efficacy. For citation: Nagornova Z.M., Kuroyedov A.V., Seleznev A.V. Comparative analysis of the efficacy and safety of fixed-dose combinations versus their individual components for open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2019;19(1):13–19.